Plastic debris collars on juvenile carcharhinid sharks (Rhizoprionodon lalandii) in southwest Atlantic - Sazima, I; Gadig, OBF; Namora, R. C.; Motta, F. S. (Elsevier B.V., 2002)
Three juvenile Brazilian sharpnose sharks (Rhizoprionodon lalandii) caught in gillnets in southeast Brazil, southwest Atlantic, were found with plastic debris rings around their gill or mouth region. The rings caused severe abrasion on the sharks' tissues as the animal grew, the collars probably hampering normal feeding and/or ventilation since two of the collared individuals were emaciated. The rings were identified as detachable lid parts from plastic bottles, likely thrown overboard by fishery and/or recreation boats. As several carcharhinid shark species dwells and reproduce in shallow waters, the impact of discarded plastic debris likely is greater on this shark type. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: southwest Atlantic; Brazilian sharpnose shark; entanglement; detachable bottle parts; plastic debris rings